No association between donor telomere length and outcomes after allogeneic unrelated hematopoietic cell transplant in patients with acute leukemia. (April 2018) - Gadalla, Shahinaz M.; Wang, Tao; Loftus, David; Friedman, Lyssa; Dagnall, Casey; Haagenson, Michael; Spellman, Stephen; Buturovic, Ljubomir; Blauwkamp, Marsha; Shelton, Jason; Fleischhauer, Katharina; Hsu, Katharine; et al.
Abstract Recent studies suggest improved survival in patients with severe aplastic anemia receiving hematopoietic cell transplant (HCT) from unrelated donors with longer telomeres. Here, we tested whether this effect is generalizable to patients with acute leukemia. From the Center for International Blood and Marrow Transplant Research (CIBMTR® ) database, we identified 1097 patients who received 8/8 HLA-matched unrelated HCT for acute myeloid leukemia (AML) or acute lymphocytic leukemia (ALL) between 2004 and 2012 with myeloablative conditioning, and had pre-HCT blood sample from the donor in CIBMTR repository. The median age at HCT for recipients was 40 years (range ≤1–68), and 32 years for donors (range = 18–61). We used qPCR for relative telomere length (RTL) measurement, and Cox proportional hazard models for statistical analyses. In a discovery cohort of 300 patients, longer donor RTL (>25th percentile) was associated with reduced risks of relapse (HR = 0.62, p = 0.05) and acute graft-versus -host disease II–IV (HR = 0.68, p = 0.05), and possibly with a higher probability of neutrophil engraftment (HR = 1.3, p = 0.06). However, these results did not replicate in two validation cohorts of 297 and 488 recipients. There was one exception; a higher probability of neutrophil engraftment was observed in one validation cohort (HR = 1.24, p = 0.05). In a combined analysis of the three cohorts, no statistically significant associations (allp > 0.1) were found between donor RTL and any outcomes.